The Assessing Promotive and Preventive Programs Efficiency in Indonesia: A Data Envelopment Analysis and Qualitative Approach - Mazda Novi Mukhlisa; Windy Haryani; Indra Yoga; Rosa Estetika; Wahyu Pudji Nugraheni (Buletin Penelitian Sistem Kesehatan, 2020)
Health Operational Aid for promotive and preventive programs increases year by year. Despite that, health outcomes remain low. The objective of our study was to measure the technical eﬃciency of public health programs. We conducted a quantitative approach using Health Production Model to measure the eﬃciency of 315 districts across 34 provinces in Indonesia. To measure the eﬃciency score, we run the Data Envelopment Analysis. We also conducted a qualitative one to explore the source of ineﬃciency by managing interviews and focus group discussion to informants from six districts. The results indicated a wide variation in eﬃciency among districts. The average eﬃciency score was 63% with minimal and maximal scores were 15% and 100%, respectively. The high performing districts were in aﬄuent or accessible areas. The qualitative analysis resulted in districts with the mixed planning process and the exact basis for budget distribution, as well as various criteria for priority setting, have higher performance than those which have not. Moreover, there were speciﬁc cases played a role in the low performing districts, such as the high-risk population in remote areas and the vaccines issues on halal status. In conclusion, districts still can improve their eﬃciency in achieving health output using their health resources. Abstrak Bantuan Opersional Kesehatan (BOK) yang digunakan untuk membantu upaya program promotif dan preventif meningkat setiap tahunnya. Akan tetapi, keluaran kesehatan tetap rendah. Tujuan analisis ini adalah menilai eﬁ siensi teknis pada program kesehatan masyarakat yang menggunakan BOK. Dengan menggunakan Model Produksi Kesehatan, kami melakukan pendekatan kuantitatif untuk mengukur skor eﬁ siensi di 315 kabupaten/kota di Indonesia. Skor tersebut diukur dengan Data Envelopment Analysis. Kami juga melakukan pendekatan kualitatif untuk menggali lebih dalam tentang sumber ineﬁ siensi dengan melakukan wawancara dan diskusi kelompok terarah kepada informan di enam kabupaten/ kota. Hasil analisis menunjukkan bahwa terdapat variasi skor eﬁ siensi antar kabupaten/kota. Rata-rata eﬁ siensi adalah 63% dengan skor minimal sebesar 15% dan maksimal sebesar 100%. Kabupaten/kota dengan skor eﬁ siensi tinggi berada di area kaya atau mudah diakses. Hasil kualitatif menunjukkan bahwa kabupaten/kota dengan perencanaan bottom-up yang dikombinasikan dengan top-down, kepastian dasar pembagian distribusi, dan beberapa kriteria untuk setting prioritas memiliki skor eﬁ siensi yang tinggi. Masalah khusus yang dihadapi kabupaten/kota juga berperan dalam ineﬁ siensi, seperti populasi berisiko tinggi di daerah terpencil atau isu halal/haram vaksin. Secara garis besar, kabupaten/ kota masih berpotensi meningkatan eﬁ siensi dalam mencapai output kesehatan dengan menggunakan sumber daya kesehatan yang dimilikinya.